Robusta Coffee-Based Village Development Through the Sustainable Livelihood Approach: Local Assets and Green Investment Pathways in Sabet Village, Aceh Jaya - Rahmat Pramulya; Sato Morihiko; Ego Ibnu Wijaksena; Tjahjo Tri Hartono; Purnomo; Elida Novita; Muhammad Reza Aulia; Dewi Fithria; Dedy Darmansyah (PT Sahabat Investasi Indotama, 2026)
Sabet Village, Jaya District, Aceh Jaya Regency, presents significant potential for Robusta coffee-based agroforestry development under social forestry arrangements. This study analyzes the livelihood asset conditions of coffee farmers in Sabet Village using the Sustainable Livelihood Approach (SLA) framework and identifies green investment pathways that can strengthen coffee-based village development. A mixed-methods research design was employed, combining household surveys, in-depth interviews, and field observations. Results indicate that financial capital scored highest (3.97), followed by physical capital (3.53), human capital (3.35), social capital (2.86), and natural capital (2.22). Key village assets include a Fine Robusta cupping score of 83.00 surpassing the international specialty threshold, functioning local institutions including Lembaga Adat (customary governance) and Baitul Mal (Islamic social finance), and a supportive regulatory framework under Qanun No. 10/2008. The low natural capital score signals ecological pressures requiring urgent intervention through sustainable agroforestry practices. Green investment opportunities from Japan, channeled through JICA, the Joint Crediting Mechanism (JCM), and Japan's Green Transformation (GX) policy, offer strategic pathways for financing land rehabilitation and enhancing the competitiveness of Sabet’s coffee in global markets. This study recommends strengthening local institutional capacity and developing asset-based financing schemes as the foundation for sustainable village development.